The Effect Of Compensation, Communication And Work Discipline On Employee Performance At PT Perkebunan Nusantara 1 Regional 7 Kebun Tulung Buyut - Yogi Apriyadi; Iskandar Ali Alam (Cita konsultindo, 2025)
This study aims to determine the effect of compensation, communication, work discipline on employee performance at PT. Perkebunan Nusantara 1 Regional 7 Kebun Tulung Buyut. This study uses a quantitative approach with SPSS analysis tools. The data quality test used is the validity test and reliability test, then the classical assumption test is carried out, namely the normality test, multicollinearity test, and heteroscedasticity test. Then, the hypothesis test carried out is the t test, then the coefficient of determination test is carried out. The population in this study was 30 respondents. The sampling technique used was a saturated sample, so all respondents were used as research samples. Based on the results of the study, it can be seen that the variablesCompensation, Communication, Discipline are positive and significant to Employee Performance of PT Perkebunana Nusantara 1 Regional 7 Kebun Tulung Buyut. It is expected that this research can be a reference for PT Perkebunana Nusantara 1 Regional 7 Kebun Tulung Buyut to pay more attention to the variables in this study.